A touchy subject: Ca2+ signaling during leaf movements in Mimosa. (March 2023) - Bakshi, Arkadipta; Swanson, Sarah J.; Gilroy, Simon
Highlights: Touch- and wound-induced leaf movements in Mimosa plants require Ca 2+ signals. Ca 2+ increases move sequentially through the pulvini, the motor organs of the leaf. Ca 2+ increases in the pulvini are required to trigger leaf movements. Mimosa's leaf movements deter insect herbivores. Abstract: Mimosa pudica, the sensitive plant, responds to stimuli such as touch and wounding with leaf movements that propagate throughout the plant. The motion is driven by changes in the turgor of specialized cells in a set of motor organs called pulvinae. By imaging cellular Ca 2+ levels as the wave of movement propagates through the leaf, Hagihara and colleagues now show that Ca 2+ signals precede and predict the pulvinar movements. These results provide compelling support for a model where Mimosa uses a Ca 2+ -related response system to trigger its leaf movements. These researchers then used CRISPR to delete a critical genetic regulator of pulvinar development, producing plants with immobile leaves. These plants experienced more herbivory than wild type, suggesting that the Ca 2+ -triggered leaf movements are an adaptation to deter herbivory. Graphical abstract: Image, graphical abstract